Peak oil, economic growth, and wildlife conservation - Trauger, David L.; Czech, Brian; Gates, J. Edward (Springer New York, 2014)
Today, there are numerous books available on the subject of Peak Oil; however, most, if not all, address the consequences of peaking on our industrialized society and how we might adapt.  There also are several excellent books available dealing with economic growth.  Books on wildlife conservation are also commonplace.  However, no book currently integrates the topics of Peak Oil, economic growth, and wildlife conservation into one narrative.  This book attempts to do just that.  The book is divided into four sections, respectively titled The Energy Dilemma, Economic Considerations, Fundamental Conflicts, and Wildlife Conservation and the Future.  Each succeeding section builds on those that come before it.  Readers of this book will gain a deeper understanding of the vital linkages between energy, economic growth, and the conservation of natural landscapes and native species. This book is written for a broad audience, including natural resources professionals, planners, and policy-makers in federal, state, and provincial governments.  Leaders of conservation and environmental organizations will value its clarion call for action to stem further losses of biodiversity (including genetic diversity) and advance its conservation. Professors teaching university courses in wildlife ecology and management, conservation biology, and ecological economics will find this volume to be an indispensable course book for their students. Others will use it as a primary reference for seminars dealing with sustainability.  Persons interested in Peak Oil and energy depletion will learn how these issues impinge on wildlife conservation.  Those interested in alternatives to a growth economy will find the discussion of a steady state economy enlightening, given that lack of cheap, abundant energy may force us in that direction anyway.  It is our hope that readers of this book will act on the information contained in it to effect positive change in how our global civilization interacts with the biosphere and humanity's co-inhabitants-the millions of species composing Earth's biodiversity.